Development of History Learning with a Scientific Approach Through Outdoor Study in Class XI IIS 4 SMA Negeri Ajibarang - Apriliana, Diah (Universitas Negeri Semarang, 2018)
This research aims to develop a history lesson in class XI social science secondary schools to overcome Ajibarang. This study uses design research and development (Research and Development). This study was conducted in Class XI social science secondary schools in Ajibarang in 2014/2015. The approach used in this study is the R and D quantitative approach with experimental design pattern Design. Pengambilan Pre Test Post Test samples were obtained from two classes of class X social science as an experimental class of carrying out the pre-test and post-test with classroom learning outside the school XI social science as the control class in the form of implementation of the pre-test and post-test with conventional learning, before doing penelitien first design learning development lecturer. Hasil, validated by the validation of the learning progression, meets the criteria of decent so that it can be tested.